2009
DOI: 10.1039/b903005k
|View full text |Cite
|
Sign up to set email alerts
|

Anion effect on radiochemical stability of room-temperature ionic liquids under gamma irradiation

Abstract: Radiochemical stability of imidazolium-based ionic liquids constituted of the BuMeIm(+) cation and associated with four commonly used anions (X(-): Tf(2)N(-), TfO(-), PF(6)(-) and BF(4)(-)) has been investigated under gamma irradiation for high irradiation doses (up to 2.0 MGy). The anion effect has been examined by quantifying the radiolytic yields of disappearance for cation and anions and by identifying corresponding radiolysis products with several analytical techniques. On the one hand, a large number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
86
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 28 publications
(24 reference statements)
8
86
0
Order By: Relevance
“…Inspection of the products listed above and the related IL structures shows that they are formed by decomposition of one or both of the anionic and cationic moieties of the ILs. Similar results were observed by Le Rouzo et al [14] during c-irradiation of an IL having the same imide anion as we have studied but a different cation. There were no noticeable changes in the gas phase product speciation with increased irradiation time suggesting that the radiolytic decomposition of the ILs reached a steady state quickly with continuous irradiation.…”
Section: Ionic Liquids In Contact With Gas Phasesupporting
confidence: 92%
See 1 more Smart Citation
“…Inspection of the products listed above and the related IL structures shows that they are formed by decomposition of one or both of the anionic and cationic moieties of the ILs. Similar results were observed by Le Rouzo et al [14] during c-irradiation of an IL having the same imide anion as we have studied but a different cation. There were no noticeable changes in the gas phase product speciation with increased irradiation time suggesting that the radiolytic decomposition of the ILs reached a steady state quickly with continuous irradiation.…”
Section: Ionic Liquids In Contact With Gas Phasesupporting
confidence: 92%
“…In the intended application, a water-IL system will be exposed to continuous ionizing radiation that can strongly influence the chemical state of the system and the chemical parameters affecting the separation efficiency of the system. Studies on the effects of radiation on the stability of ILs are rare and have been limited to studies of pure IL phases [11][12][13][14][15][16][17]. These studies, mostly confined to ammoniumbased ILs (AILs), have shown that ILs are relatively radiation resistant, compared to water or organic solvents, because of the smaller probability of 'dry' electrons escaping geminate or recombination reactions before they are solvated [9,15].…”
Section: Introductionmentioning
confidence: 99%
“…ILs have intrinsic ionic conductivity at room temperature and thus can offer, unlike molecular solvents, a wide electrochemical window which can be harnessed in several processes [4][5][6]. Also their chemical and physical properties are tunable by selection of suitable cation and anion [7][8][9][10]. Owing to these advantages, ILs find many applications as novel solvents in organic synthesis and separation processes [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 98%
“…For these reasons, they are currently considered as ''green'' solvents to replace the traditional solvents, especially the volatile organic compounds, in many fields: organic and inorganic synthesis, catalysis, polymerization and various electrochemical devices [5]. They are also under investigation in the field of nuclear power industry, as recent work has shown their good stability under a, b and c irradiation [5][6][7][8][9]. Indeed, ILs could be involved in some specific steps of separation or purification of actinides in the frame of nuclear fuel reprocessing, especially in electrodeposition processes.…”
Section: Introductionmentioning
confidence: 99%